Computer simulation of humanitarian scenarios: tools for training and field management in relief agencies - Benini, Aldo A.; Benini, Janet K. Bradford (1999)
Computer simulation, a technology well advanced in military strategies and tactics, has been used for response to natural disasters. The authors argue that it should also be applied to the field of humanitarian action in armed conflict. Projected uses are: the management and planning of relief actions, public resource mobilization for humanitarian actions, and training personnel for violent work environments. How that can happen is shown with the example of a real relief management problem in the Sudan. Simulation can be introduced in ways that are compatible with agencies' needs, communication styles,and staff abilities. Several factors speak for it: many agencies routinely use computer applications that are flexible enough for simulation to be added seamlessly. Simulation will help agencies to add the power of analysis to the images that prompt humanitarian actions. And with violence and chaos continuing, simulation offers a technique around which to share expertise and training in new, networked partnerships. - Reproduced
Keywords: Disaster relief